Analisa Pemenuhan Hak Masyarakat Berkebutuhan Khusus di Kabupaten Ponorogo - Imamudin, Iqbal Akbar; Mahardhani, Ardhana Januar; Cahyono, Hadi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
The focus of this research is on the role of the village government in guaranteeing and fulfilling the disability rights needs of people with mental retardation. This study uses qualitative methods, research data obtained through the methods of observation, interviews, and documentation as well as data analysis techniques that researchers use in this study is using an interactive model. This research was conducted in Karangpatihan Village, Balong District, Ponorogo Regency which has 97 mentally retarded persons in 2020. The results of this study indicate that the Karangpatihan Village government has given rights to mentally retarded persons with twenty-two types of rights in accordance with Law number 8 of 2016 on Persons with Disabilities. Furthermore, in its implementation, the Karangpatihan Village Government also collaborates through the triple helix concept, namely between academics, business, and the third government, synergizing with each other to provide the best services for people with disabilities.